Sistem Informasi Rawat Jalan Pasien Rumah Sakit Umum Daerah (RSUD) dr. Chasbullah Kota Bekasi Berbasis Java - Muhammad Ilham Insani; Lusi Ariyani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to simplify the management of dr. Chasbullah Kota Bekasi hospital outpatient service data. so that work becomes effective and efficient, in addition to the design of this application can also help solve work problems related to reports that can be completed quickly, precisely and accurately. The research method used in this Hospital outpatient service application system is Grounded Research which is based on facts and uses comparative analysis with the aim of conducting empirical generation, establishing concepts, proving theories, developing theories, collecting data and analyzing data at the same time. In addition, the author also collected data through direct observation, interviews, literature studies, and documentation to obtain the required information. After conducting the research, the author concluded that the Hospital Outpatient application system can help data processing become more effective and efficient.